Combination of Photon and Carbon Ion Irradiation with Targeted Therapy Substances Temsirolimus and Gemcitabine in Hepatocellular Carcinoma Cell Lines - Dehne, Sarah; Fritz, Clarissa; Rieken, Stefan; Baris, Daniela; Brons, Stephan; Haberer, Thomas; Debus, Jürgen; Weber, Klaus-Josef; Schmid, Thomas E.; Combs, Stephanie E.; Habermehl, Daniel (Frontiers in Oncology, 2017)
Background This work investigates on putative cytotoxic effects in four different Hepatocellular Carcinoma cell lines after irradiation with photons or carbon ions in combination with new targeted molecular therapy using either Temsirolimus (TEM) or Gemcitabine (GEM). Methods and Materials The HCC cell lines HepG2, Hep3B, HuH7 and PLC were cultured and irradiated with photons or carbon ions at the Heidelberg Ion beam Therapy center using the raster scanning method. For combination experiments, cell lines were first treated with Temsirolimus or Gemcitabine before irradiation. Cytotoxicity was measured by a clonogenic survival assay. The evaluation of the experiments and the obtained survival curves were based on the concept of additivity defined by Steel and Peckham. Results The results for the combination of carbon ions and both tested systemic substances TEM and GEM showed independent toxicities in all four cell lines. Supra-additive effects were observed in PLC cells for photon irradiation combined either with TEM or GEM and in HuH7 cells for the combination of photons with TEM. Conclusion Addition of targeted therapy substances Temsirolimus and Gemcitabine to photon irradiation showed additive cytotoxicity in HCC cell lines whereas independent toxicities where reached by the combination of carbon ions to these substances. It can be assumed that combining 12C with systemic substances only has independent effects because heavy ions cause direct damage because of their high-LET character resulting in complex and clustered double-strand breaks. Nonetheless, further investigations are warranted in order to determine whether addition of systemic therapy allows a reduction of radiation doses in combination therapy. This could possibly lead to better responses and tolerances in patients with HCC.